Impactos provenientes da redocumentarização de acervos permanentes na pesquisa histórica - Hercules Pimenta dos Santos (2018)
The present research is the result of the development of an interdisciplinary study that sought to elucidate the impacts found in the process of consultation and organization of the archival document of permanent age, digitized. We sought to analyze ways of organizing the documentation of permanent age developed in Spain, in relation to the Brazilian information units. The study processes in Spain, after applied in Brazil, aimed search for contrasts and approximations in relation to the procedures between the two academic traditions. From the perspective of the Digital Humanities studies, one of the main objectives of the work was to systematize issues debated in the field of the digitization of permanent collections and to collaborate with new reflections for both main focus areas: Archival and History. His starting point rested on the following hypothesis: the digitization of the archives of permanent age positively and negatively impacts on the historiographical making and in the archival documentary organization. The objective was to broaden the understanding of new concepts, such as Redocumentarization, and the impacts of the present expansion of circulation and access to archival documents via the virtual medium. The investigation is based on the theoretical methodological deepening that comprised three essential moments: bibliographic research, observation and interviews, for the collection of empirical data. We established stages for exploratory purposes, aiming to visit teams for the development of theoretical, instrumental and documentary research projects. The professionals selected for the interviews formed a group with diverse profiles and were intentionally defined for the sample. Some of the results obtained, as a result of the methodological procedure applied, allowed us to infer that the structural changes in the informational process caused by the digitalization of documents and electronic communication brought definitive impacts on the configuration of the documents, in general, including their internal and logical structure operation. We have observed that until now, and mainly due to the fluidity offered by digital technologies, it would not be possible to maintain a definition of the Document Entity in a hermetic sense, since this has been fading faster and faster, by easily incorporating new elements influenced by the dynamism of the digital universe. From this discussion, we recorded examples of the existence of different views being generated from the same documentation, as well as verifying that the virtualization and remote access of the collections may suggest an emptying of the Files. We believe that it is important that in the two focused academic formations, Archivology and History, there are disciplines that contemplate some gaps generated for both of them. We have found that the need for the Archives to duplicate a part of their collections by the digitalization, has brought new challenges for the Archivology professional as a consequence. It was possible to perceive the emergence of some political issues inherent in the general treatment of the collections. Moreover, among the main objectives of this study, we can say that are generated by means of the digitization of permanent collections, as well as great benefits, problems and issues that merit in-depth reflection.